2020
DOI: 10.1111/ecca.12339
|View full text |Cite
|
Sign up to set email alerts
|

‘Trophy Architects’ and Design as Rent‐seeking: Quantifying Deadweight Losses in a Tightly Regulated Office Market

Abstract: Britain tightly restricts the supply of office space, creating substantial economic rents, but its development restrictions are politically administered and therefore gameable, inducing rent‐seeking activity. We find that ‘trophy architects’ (TAs)—prior winners of a lifetime achievement award—obtain more space on a given site apparently by signalling architectural merit. Analysis of 2039 office buildings shows that TAs build 14 stories taller, thereby increasing a representative site value by 152% and capturin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…If a project is rejected this can be appealed in a quasi-judicial process first to the Planning Inspectorate and ultimately to the government minister responsible for the planning system. Thus, all decisions about development are uncertain because they are political decisions, so subject to lobbying and the personal tastes or prejudices of local representatives: moreover, only a minority of LPAs in fact have an up to date local plan and such plans are not binding (see Cheshire & Carozzi, 2019). So not only are all decisions uncertain but they are also gameable.…”
Section: The British Planning System: Permitted Development Rightsmentioning
confidence: 99%
See 4 more Smart Citations
“…If a project is rejected this can be appealed in a quasi-judicial process first to the Planning Inspectorate and ultimately to the government minister responsible for the planning system. Thus, all decisions about development are uncertain because they are political decisions, so subject to lobbying and the personal tastes or prejudices of local representatives: moreover, only a minority of LPAs in fact have an up to date local plan and such plans are not binding (see Cheshire & Carozzi, 2019). So not only are all decisions uncertain but they are also gameable.…”
Section: The British Planning System: Permitted Development Rightsmentioning
confidence: 99%
“…It is included here, interacted with entitlement, to see whether the premium for the PDR was greater for office buildings in these more restrictive boroughs. A number of studies (see Cheshire & Dericks, 2020) have found office prices are higher, the higher is the local density of office-based employment. So that, too, is included using data from Nomis (2011).…”
Section: Number Of Elevatorsmentioning
confidence: 99%
See 3 more Smart Citations